Production of Triple-Gene (GGTA1, B2M and CIITA)-Modified Donor Pigs for Xenotransplantation - Xu, Kaixiang; Yu, Honghao; Chen, Shuhan; Zhang, Yaxuan; Guo, Jianxiong; Yang, Chang; Jiao, Deling; Nguyen, Tien Dat; Zhao, Heng; Wang, Jiaoxiang; Wei, Taiyun; Li, Honghui; et al. (Frontiers in Veterinary Science, 2022)
Activation of human immune T-cells by swine leukocyte antigens class I (SLA-I) and class II (SLA-II) leads to xenograft destruction. Here, we generated the GGTA1, B2M, and CIITA (GBC) triple-gene-modified Diannan miniature pigs, analyzed the transcriptome of GBC-modified peripheral blood mononuclear cells (PBMCs) in the pig's spleen, and investigated their effectiveness in anti-immunological rejection. A total of six cloned piglets were successfully generated using somatic cell nuclear transfer, one of them carrying the heterozygous mutations in triple genes and the other five piglets carrying the homozygous mutations in GGTA1 and CIITA genes, but have the heterozygous mutation in the B2M gene. The autopsy of GBC-modified pigs revealed that a lot of spot bleeding in the kidney, severe suppuration and necrosis in the lungs, enlarged peripulmonary lymph nodes, and adhesion between the lungs and chest wall were found. Phenotyping data showed that the mRNA expressions of triple genes and protein expressions of B2M and CIITA genes were still detectable and comparable with wild-type (WT) pigs in multiple tissues, but α1,3-galactosyltransferase was eliminated, SLA-I was significantly decreased, and four subtypes of SLA-II were absent in GBC-modified pigs. In addition, even in swine umbilical vein endothelial cells (SUVEC) induced by recombinant porcine interferon gamma (IFN-γ), the expression of SLA-I in GBC-modified pig was lower than that in WT pigs. Similarly, the expression of SLA-II DR and DQ also cannot be induced by recombinant porcine IFN-γ. Through RNA sequencing (RNA-seq), 150 differentially expressed genes were identified in the PBMCs of the pig's spleen, and most of them were involved in immune- and infection-relevant pathways that include antigen processing and presentation and viral myocarditis, resulting in the pigs with GBC modification being susceptible to pathogenic microorganism. Furthermore, the numbers of human IgM binding to the fibroblast cells of GBC-modified pigs were obviously reduced. The GBC-modified porcine PBMCs triggered the weaker proliferation of human PBMCs than WT PBMCs. These findings indicated that the absence of the expression of α1,3-galactosyltransferase and SLA-II and the downregulation of SLA-I enhanced the ability of immunological tolerance in pig-to-human xenotransplantation.